Peran Bank Syariah dan UMKM dalam Meningkatkan Perekonomian Indonesia - Ernayani, Rihfenti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Businesses that are carried out to meet the needs of life include conducting Micro, Small and Medium Enterprises. The purpose of this study is to analyze the role of Islamic banks and MSMEs in improving the Indonesian economy. The method in this article is a qualitative method with literature study or Library Research. The purpose of this article is to analyze existing theories by looking at their comparison with previous theories in the research literature. The literature used is literature from research results or reviews that are recorded in national and international scientific articles related to financial management. All articles used are sourced from the electronic literacy data search engine Mendeley and Google scholar. The results showed that with Islamic sharia principles, Islamic banking plays an important role in driving the wheels of the Indonesian economy through the development and empowerment of MSMEs.